Psychosocial Condition and Parenting Self-Efficacy Among Postpartum Mothers - Oktafia, Riski; Rahmayanti, Rini; Maghpira, Dea Ainun; Indriastuti, Nur Azizah (Universitas Aisyah Pringsewu, 2022)
The postpartum period is a transitional period of changing roles for parents. Postpartum mothers need to have confidence in their ability to care for and nurture babies. Psychosocial conditions are one of the causes of problems in achieving her new role as a mother and babysitting. The study's focus was to determine the relationship of psychosocial conditions with parenting self-efficacy among postpartum mothers. This study is a correlational quantitative study with a cross-sectional approach. Sampling using purposive sampling of 107 respondents in postpartum mothers. The instrument used to measure psychosocial conditions uses the postnatal risk questionnaire (PNRQ) instrument and the parenting self-efficacy using the self-efficacy parenting scale (PSES) instrument. The statistical test in this study is spearman rank. The results showed that postpartum mothers had psychosocial conditions at risk of 36 (33.6%) and were not at risk by 71 (66.4%). Postpartum mothers had high self-efficacy parenting 98 (91.6%) and low 9 (8.4%). The results of the statistical test showed p-value= 0.000 and correlation coefficient= 0.426. There is a significant association of psychosocial conditions with self-efficacy parenting in postpartum mothers. Nurses need to identify the psychosocial condition of postpartum mothers and improve parenting self-efficacy towards the care of mothers and their babies. Abstrak: Periode pascapersalinan merupakan masa transisi perubahan peran menjadi orang tua. Ibu pasca persalinan perlu memiliki keyakinan terhadap kemampuan dalam merawat dan mengasuh bayi. Kondisi psikososial merupakan salah satu penyebab masalah dalam mencapai peran barunya sebagai seorang ibu dan pengasuhan bayi. Tujuan penelitian ini mengidentifikasi hubungan kondisi psikososial dengan parenting self-efficacy pada ibu pascapersalinan. Penelitian ini merupakan penelitian kuantitaif korelasional dengan pendekatan cross-sectional. Pengambilan sampel menggunakan purposive sampling sejumlah 107 responden pada ibu pascapersalinan. Instrumen yang digunakan untuk mengukur kondisi psikososial menggunakan instrumen postnatal risk questionnaire (PNRQ) dan parenting self-efficacy menggunakan instrumen self efficacy parenting scale (PSES). Uji statistik dalam penelitian ini adalah spearman rank. Hasil penelitian menunjukkan ibu pascapersalinan memiliki kondisi psikososial beresiko sebesar 36 (33,6%) dan tidak berisiko sebesar 71 (66,4%). Ibu pascapersalinan memiliki parenting self-efficacy yang tinggi 98 (91,6%) dan rendah 9 (8,4%). Hasil uji statistik menunjukkan p-value= 0,000 dan koefisien korelasi= 0,426. Terdapat hubungan yang signifikan terhadap kondisi psikososial dengan parenting self-efficacy pada ibu pascapersalinan. Perawat perlu mengidentifikasi kondisi psikososial ibu pascapersalinan dan meningkatkan parenting self-efficacy terhadap perawatan ibu dan bayinya.